Representation of the Exploitation of Women in Religious Institutions in the Film “Maharaj” - Sindi Artika; Fakhrur Rozi (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
The exploitation of women within religious institutions is driven by patriarchy and the manipulation of religion, resulting in sexual violence, discrimination, and systemic gender injustice. This study discusses the film Maharaj as a medium that reveals the exploitation of women and critiques patriarchal religious institutions. This research uses a qualitative descriptive method with semiotic analysis. Data collection was carried out through observation and documentation. Triangulation of techniques and time was used to ensure data validity. Research findings show that the film Maharaj reveals the exploitation of women in religious institutions through visual symbolism, body gestures, and rituals such as Charan Seva, which reflect patriarchal and spiritual domination legitimized by culture. The representation of submissive and silent women becomes a marker of systemic oppression. A cultural feminist approach is used to highlight the courage of women to resist this structure. The spiral of silence theory explains the victims’ silence as a result of social and religious stigma. Karsandas Mulji appears as a symbol of resistance, opening space for discourse through media. This film acts as a form of social criticism that calls for critical awareness, justice, and gender equality. Conclusion: The film highlights the exploitation of women in religion and presents resistance as a form of social critique for gender equality.